IMPLEMENTASI MANAJEMEN BERBASIS TUJUAN PADA MODEL PEMBELAJARAN DIGITAL BERBANTUAN GAME EDUKATIF MAZE UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA DI SMPN 3 CIPARAY DAN SMP AL-QONAAH BALEENDAH KABUPATEN BANDUNG - PUTRA, DENI; Mardiana, Dinny; Soro, Suharyanto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The implementation of digital learning in schools has not been optimal in improving students’ critical thinking skills because technology is still used merely as a medium, has not been managed systematically or in a goal-oriented manner, and has not effectively promoted higher-level cognitive engagement in line with the demands of the Merdeka Curriculum and the development of High Order Thinking Skills. This study aims to examine the implementation model of digital learning based on the Maze educational game in improving students’ critical thinking skills through a Management by Objectives approach. The study employs a qualitative case study design using observation, interviews, and documentation with thematic analysis. The findings indicate that Maze-based learning is planned systematically with measurable objectives, implemented in an active and student-centered manner, and supported by continuous monitoring and evaluation. Supporting factors include teachers’ digital literacy, school principal leadership, the availability of digital facilities, and a collaborative culture, while inhibiting factors include technical constraints, differences in students’ abilities, and limited instructional time.